2020
DOI: 10.3390/ijms21030789
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal HDL Counteracts Placental Vascular Inflammation via S1P–S1PR1 Axis

Abstract: Placental inflammation and dysfunction during pregnancy are associated with short- and long-term adverse outcomes for the offspring. However, the mechanisms of vascular protection at the feto-placental interface are still poorly investigated. The high-density lipoprotein (HDL) associated sphingosine-1-phosphate (S1P) has been described as a powerful anti-inflammatory complex. This study aimed to elucidate the role of cord blood-derived HDL (nHDL) in feto-placental endothelial dysfunction. Here, we report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Moreover, Del Gaudio and colleagues observed that fetal HDL induces vasorelaxation of precontracted placental chorionic arteries [ 134 ]. The same authors further investigated the role of cord blood-derived HDL and S1P on the fetoplacental endothelium [ 138 ]. Primary fetal placental endothelial cells were approached by and challenged with TNFα to induce inflammation.…”
Section: The Role Of Cord Blood-derived Hdl In Maintaining Fetoplacental Vascular Integritymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, Del Gaudio and colleagues observed that fetal HDL induces vasorelaxation of precontracted placental chorionic arteries [ 134 ]. The same authors further investigated the role of cord blood-derived HDL and S1P on the fetoplacental endothelium [ 138 ]. Primary fetal placental endothelial cells were approached by and challenged with TNFα to induce inflammation.…”
Section: The Role Of Cord Blood-derived Hdl In Maintaining Fetoplacental Vascular Integritymentioning
confidence: 99%
“…Primary fetal placental endothelial cells were approached by and challenged with TNFα to induce inflammation. They showed that incubation with fetal HDL-S1P complex from healthy donors diminished the ability of TNFα to activate signaling of NF-κB and expression of pro-inflammatory markers [ 138 ]. Angiotensin II is a stimulator of NADPH oxidase, which produces reactive oxygen species, leading to a vascular inflammatory response [ 139 ].…”
Section: The Role Of Cord Blood-derived Hdl In Maintaining Fetoplacental Vascular Integritymentioning
confidence: 99%
See 3 more Smart Citations